Pengaruh Stres Kerja Dan Kerjasama Tim Terhadap Kinerja Perawat Poli Rawat Jalan RSU Kota Tangerang Selatan - Dede Rusmanto; Irfan Rizka Akbar (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
The purpose of this study is to determine the effect of Work Stress and Teamwork on the Performance of Outpatient Clinic Nurses at RSU Kota Tangerang Selatan, both partially and simultaneously. This study uses a quantitative research method with a sample of 58 respondents. The data analysis techniques employed include validity testing, reliability testing, normality testing, multicollinearity testing, autocorrelation testing, heteroscedasticity testing, simple linear regression analysis, multiple linear regression analysis, simple correlation coefficient analysis, multiple correlation coefficient analysis, coefficient of determination analysis, t-test, and F-test. Based on the results of the t-test, the calculated t-value for the work stress variable (X1) is 4.977 > 2.003, with a significance value of 0.000, which is smaller than the probability value of 0.05 (0.000 < 0.05). This indicates that work stress has a positive and significant effect on the performance of outpatient clinic nurses (Y). Furthermore, the t-test results show that the calculated t-value for the teamwork variable (X2) is 5.713 > 2.003, with a significance value of 0.000, which is smaller than 0.05 (0.000 < 0.05). This means that teamwork has a positive and significant effect on the performance of outpatient clinic nurses (Y). Based on the F-test results, work stress (X1) and teamwork (X2) simultaneously have a significant effect on the performance of outpatient clinic nurses (Y), as evidenced by an F coefficient value of 25.355 > 3.16 with a significance value of 0.000 < 0.05. It can be concluded that work stress (X1) and teamwork (X2) simultaneously have a positive and significant effect on the performance of outpatient clinic nurses at RSU Kota Tangerang Selatan (Y).